Determination of Sensitive Proteins in Beer by Nephelometry: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Batchvarov, V.; Kellner, V. (BrewingScience, 2002)
The EBC Analysis Committee decided to test a modification of Chapon’s method (2, 3) for the determination of sensitive proteins in beer by nephelometry. In autumn 2001 a collaborative trial was carried out using six beer samples with different levels of sensitive proteins. Sixteen laboratories of the members of the EBC Analysis Committee took part in the collaborative trial.